2007
DOI: 10.3171/jns-07/07/0060
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow disturbance in perforating arteries attributable to aneurysm surgery

Abstract: The patency of the perforating artery cannot be determined by intraoperative microscopic inspection. Intraoperative motor evoked potential monitoring contributed to the detection of blood flow disturbance in the territory of the AChA and LSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 29 publications
1
39
0
4
Order By: Relevance
“…Among patients with cerebral aneurysm, 5.2% have been found to exhibit residual aneurysms and 4.4% experience cerebral infarction because of blood flow disturbance in perforating arteries after microneurosurgical treatment. 1,2 To our knowledge, however, only a few studies have examined the methods for direct and rapid detection of residual aneurysms and the prediction of ischaemic events.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with cerebral aneurysm, 5.2% have been found to exhibit residual aneurysms and 4.4% experience cerebral infarction because of blood flow disturbance in perforating arteries after microneurosurgical treatment. 1,2 To our knowledge, however, only a few studies have examined the methods for direct and rapid detection of residual aneurysms and the prediction of ischaemic events.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Nevertheless, it is possible that the LSA blood flow will be disturbed during aneurysm surgery, resulting in focal ischemia. 21 The most proximal LSA in our study were observed to originate only 2-3 mm from the carotid bifurcation. In addition, the curves or loops of some LSA were positioned just superior or lateral to the ICA bifurcation.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, the radiologists and neurosurgeons sometimes register a compression of the thin-walled LSAs by an aneurysm of the parent vessel, which is accompanied by the capsular or ganglionic ischaemia [21,24]. The LSAs can also be damaged or become less patent in the course of neurovascular operations, for instance, when dissecting the perforating vessels from the wall of an aneurysm, placing a clip on the aneurysm neck, or applying a temporary MCA occlusion, as well as by direct iatrogenic injury to the LSAs [7].…”
Section: Discussionmentioning
confidence: 99%